Implementasi Internet of Things (Iot) pada Sistem Penyiraman Otomatis Bibit Alpukat dengan Aplikasi Mobile - Adigunawan, Adigunawan; Tjahjono, Budi; Irawan, Bambang; Prabowo, Ary (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to develop an Internet of Things (IoT)-based automatic watering system with real-time monitoring features for soil moisture and pH levels, designed to support the cultivation of avocado seedlings. The system utilizes an ESP32 microcontroller connected to two soil moisture sensors and one pH sensor, and is controlled through a mobile application built with Flutter. Sensor data is transmitted to a backend server using the MQTT protocol, while communication between the application and the backend server is conducted via a REST API. Users can configure watering schedules and durations, as well as set moisture thresholds to trigger automatic watering. Testing results show that the system functions effectively in monitoring soil conditions and performing watering based on the configured settings.